Development and Testing of Multi-Microbial Strain Biopesticides Against Spodoptera litura F. and Plutella xylostella L. under Laboratory Conditions - Lan, Tran Thi; Hai, Pham The; Minh, Nguyen Hong; Giang, Ho Thi Thu; Khanh, Nguyen Duc; Thao, Nguyen Kim Nu (VNU Journal of Science: Natural Sciences and Technology, 2025)
In Vietnam, there is a growing demand for safe vegetable production, leading to the need for biological agents as alternatives to pesticides. As a result, biopesticides have gained significant attention in research worldwide. Most microbial solutions for pest control developed so far have been based on single cultures, which limits their effectiveness. In this study, various mixed cultures of Bacillus thuringiensis ( Bt ) strains TN0017 and TN0020, Metarhizium anisopliae strain TN0024, and Beauveria bassiana strain PAM21, were developed and investigated their potential for controlling Spodoptera litura F. and Plutella xylostella L. on vegetables. The tested mixed cultures included combinations of two strains: one Bt strain and one fungal strain, as well as combinations of three strains: one Bt strain and two fungal strains. The results demonstrated that the two most effective combinations were HH3-SK (TN0020 + TN0024 + PAM21) and HH3-ST (TN0017 + TN0024 + PAM21) at a concentration of 10 8 spores/g under conditions of 25 ± 1 o C and 70 ± 5% humidity. At 96 hour post-treatment, HH3-SK achieved an 85% mortality rate for  S. litura , while HH3-ST achieved an 83.33% mortality rate for P. xylostella . Additionally, both combinations reached a mortality rate of 91.67% for S. litura and P. xylostella after 120 hour of treatment. This result demonstrates that utilizing multi-strain microbial products can promote synergistic effect and complementary interactions among the strains to enhance overall insecticidal effectiveness, representing a promising novel approach for developing biopesticides.